Perbandingan Keterbacaan Buku Anak Digital Berdasarkan Grafik Fry dan Grafik Raygor - Marlian, Marlian; Yudono, Kristophorus Divinanto Adi (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the readability level of children's books using the Fry Graph and Raygor Graph to determine the suitability of reading materials for elementary school grade levels. This study employed a quantitative descriptive approach with seven children's books as the research objects. The readability analysis was based on the average number of syllables, sentences, and difficult words in every 100 words from each analyzed book. The results indicate that six out of seven analyzed books have a readability level appropriate for third-grade elementary students based on both formulas. Meanwhile, one book demonstrates a readability level corresponding to sixth-grade students, indicating higher linguistic complexity compared to the others. These findings suggest that not all children's books are automatically suitable for their intended grade level. Therefore, readability analysis is necessary in selecting reading materials to ensure alignment between text difficulty and students’ reading abilities in elementary education.